IBM Power Systems Virtualization Operation Management for SAP Applications - Quintero, Dino; Joedecke, Enrico; Probst, Katharina; Schauberer, Andreas (IBM Redbooks, 2020)
Businesses are using IBM® Power Systems servers and Linux to consolidate multiple SAP workloads onto fewer systems, increasing infrastructure utilization; reliability, availability, and serviceability (RAS); and scalability, and reducing cost. This IBM Redpaper Redbooks publication describes key hardware and software components of an SAP solution stack. Furthermore, this book addresses non-functional items like RAS, security, and issue handling. Practical help for planning, implementation, configuration, installation, and monitoring of a solution stack are provided. This publication addresses topics for sellers, IT architects, IT specialists, and anyone who wants to implement and manage SAP workloads on IBM Power Systems servers. Moreover, this guide provides documentation to transfer how-to skills to the technical teams, and it provides solution guidance to the sales team. This publication complements documentation that is available at IBM Knowledge Center, and it aligns with educational materials that are provided by IBM Systems.
Online resource; Title from title page (viewed March 3, 2020)
Keywords: Linux; SAP HANA (Electronic resource); Virtual computer systems; Information technology -- Management; Client/server computing; Business enterprises -- Computer networks -- Management; Systèmes virtuels (Informatique); Technologie de l'information; Gestion; Architecture client-serveur (Informatique); Entreprises; Réseaux d'ordinateurs; Gestion; Information technology; Management; Business enterprises; Computer networks; Management